Miniaturized rat‐race hybrid incorporating six lumped‐element components. Issue 5 (21st March 2016) - Tang, Bo; Hayashi, Hitoshi; Ueda, Ryo
ABSTRACT: This letter presents the simulation and measurement results for a miniaturized rat‐race hybrid using six lumped‐element components. The hybrid was implemented on an FR4 substrate using chip inductors and chip capacitors. For the 530‐ to 620‐ MHz frequency range, the rat‐race hybrid exhibited power splits of −3.4 ± 0.7 dB, return losses of >18 dB, an isolation between output ports of >24 dB, and errors in the desired relative phase difference between output ports of <5°. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:1125–1128, 2016